(untitled) (European Journal of Pure and Applied Mathematics, 2013)
In this paper, we take into account the opinion of involute-evolute curves which lie on fullyÂ surfaces and by taking into account the Darboux frames of them we illustrate these curves asÂ special involute-evolute partner D-curves inÂ E3. Besides, we .nd the relations between theÂ normal curvatures, the geodesic curvatures and the geodesic torsions of these curves. Finally,Â some consequences and examples are given. Â